2018
DOI: 10.2134/jeq2018.01.0036
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐Analysis on the Effect of Agricultural Conservation Practices on Nutrient Loss

Abstract: Conservation practices are widely used to reduce N and P loads from agricultural fields and minimize their impact on water quality, but research using field‐scale data to model the national average impact of conservation practices for different forms of N and P is needed. Thus, we quantified the effects of conservation practices (grassed waterways, terraces, contour farming, filter strips, and riparian buffers) on total, particulate, and dissolved N and P runoff from farmlands. Specifically, we conducted a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to Belay et al [261], in supplementary irrigation vegetable production systems, CA practices can optimize nutrient use by decreasing nutrient losses through runoff and leaching. In this respect, several studies show that CA practices reduce the loss of nutrients via runoff or nutrients adsorbed in sediments lost by water erosion [176,[262][263][264][265]. In this context, Jordan et al [266] registered an 81% decrease in total P loss and a 94% decrease in organic nitrogen with non-inversion tillage compared with plow.…”
Section: Nutrient Availabilitymentioning
confidence: 99%
“…According to Belay et al [261], in supplementary irrigation vegetable production systems, CA practices can optimize nutrient use by decreasing nutrient losses through runoff and leaching. In this respect, several studies show that CA practices reduce the loss of nutrients via runoff or nutrients adsorbed in sediments lost by water erosion [176,[262][263][264][265]. In this context, Jordan et al [266] registered an 81% decrease in total P loss and a 94% decrease in organic nitrogen with non-inversion tillage compared with plow.…”
Section: Nutrient Availabilitymentioning
confidence: 99%
“…Once this difference was accommodated, the researchers determined that particulate P was reduced by 58% and total P by 76% when CPs were used either individually or in combination. Daryanto et al (2017) demonstrated the importance of cropping system to P loss, as did Nummer et al (2018).…”
Section: Implementing Conservation Practice Systemsmentioning
confidence: 93%
“…Often, addressing P losses at the field scale will require implementation of multiple CPs that address different P loss pathways. Nummer et al (2018) used a meta‐analysis approach to evaluate the effects of CPs (namely, conservation tillage, buffers, grassed waterways, and terraces), implemented alone or in combination, on P losses using data from the Measured Annual Nutrient loads from AGricultural Environments (MANAGE) database. Initial analysis revealed that more fertilizer was applied to fields in the database with CPs (e.g., cropland vs. pasture), thus confounding results due to the opposite effects of fertilizer application and CPs.…”
Section: Implementing Conservation Practices That Reduce Agriculturalmentioning
confidence: 99%
“…Specifically, Harmel (2015a, 2015b), Christianson et al (2016), and Hertzberger et al (2019aHertzberger et al ( , 2019b added data from 79 studies of drainage N and P concentrations and loads mainly from the midwestern and eastern United States. In addition, the MANAGE database has been used for meta-type analyses of management impacts on drainage nutrient losses (Flores et al, 2021;Hertzberger et al, 2019a;Liu et al, 2021;Zhao et al, 2016) and on the impact of agricultural conservation practices on nutrient losses in surface runoff (Nummer et al, 2018;Qian & Harmel, 2016;Reckhow et al, 2009). The database has also been used to evaluate modeling tool predictions of best management practices effectiveness, regional water balances, and regional ranges of runoff, sediment, and nutrient loss (e.g., Merriman et al, 2009;White et al, 2010White et al, , 2015aWhite et al, , 2015b.…”
Section: Introductionmentioning
confidence: 99%